Forccheimer Flow of Williamson Nano Fluid Over a Stretching Sheet With Cattaneo-Christov Heat Flux in Saturated Porous Media - Pushpalatha, Ch.; Kumar, Ch. Kishore; Shankar, B. (Communications in Mathematics and Applications, 2023)
The present study deals with heat transmission of a Williamson nanofluid on a porous plate in a Darcy-Forccheimer flow through Cattaneo-Christov heat flux, velocity, temperature and concentration slips. The basic leading equations were converted by means of similarity transformations. Later, obtained equations were resolved by “Runge-Kutta-Felhberg Method”. The velocity, temperature and the concentration profiles were driven clearly and discussed thoroughly. The values of Nusselt number and reduced Sherwood no were given in tabulated form.